Suspicious Success - Cheating, Inequality Acceptance, and Political Preferences - Felix Klimm (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Supporters of left-wing parties typically place more emphasis on redistributive policies than right-wing voters. I investigate whether this difference in tolerating inequality is amplified by suspicious success - achievements that may arise from cheating. Using a laboratory experiment, I exogenously vary cheating opportunities for stakeholders who work on a real effort task and earn money according to their self-reported performances. An impartial spectator is able to redistribute the earnings between the stakeholders, although it is not possible to detect cheating. I find that the opportunity to cheat leads to different views on whether to accept inequality. Left-wing spectators substantially reduce inequality when cheating is possible, while the treatment has no significant effect on choices of right-wing spectators. Since neither differences in beliefs nor differences in norms about cheating can explain this finding, it seems to be driven by a difference in preferences. These results suggest that redistributive preferences will diverge even more once public awareness increases that inequality may be to a certain extent created by cheating.
Keywords: C91; D63; D83; H23; H26; 330; cheating; inequality; fairness; political preferences; redistribution